Classroom Management in Improving the Learning Outcomes: A Multi-site Study in Bhayangkari Kindergarten and Tondano Bethlehem Kindergarten - Kuron, Queen; Sumual, Shelty D. M.; Tuerah, Roos M.S. (AIBPM Publisher, 2022)
This study aims to analyze the planning, implementation, and evaluation of class management in improving learning outcomes in Bhayangkari kindergarten and Bethlehem Tondano kindergarten. This research was conducted using a qualitative method with a multi-site study model. The results of this study show that 1) Classroom management planning starts from school curriculum documents. 2) The implementation of classroom management in both schools is manifested in every learning activity. 3) The evaluation of class management In both schools departed from the results of the supervision of the principal, supervisor, teacher meetings, and was evident in the learning outcomes of students. 4) Good class management will make student learning outcomes increase and develop in a good direction as well. The study indicates that classroom management affects learning outcomes. Keywords: Classroom Management, Learning Outcomes, Early Childhood Education